Paediatric Behçet's disease presenting with recurrent papillitis and episcleritis: a case report. - Parentin, Fulvio; Lepore, Loredana; Rabach, Ingrid; Pensiero, Stefano (J Med Case Rep, 2011)
INTRODUCTION: Behçet's disease is a chronic multisystem vasculitis characterized by mucocutaneous, articular, neurological, gastrointestinal and ophthalmological lesions. Ocular involvement is mainly represented by recurrent uveitis, especially posterior uveitis; however, iridocyclitis, retinal and choroidal vasculitis, optic neuritis and retinal vascular occlusion can also occur. CASE PRESENTATION: A 12-year-old Caucasian boy with a history of recurrent buccal aphthosis and nonspecific gastrointestinal symptoms was admitted to our hospital with blurred vision associated with acute episcleritis and papillitis. The patient's pathergy test was positive, suggesting a diagnosis of Behçet's disease. Corticosteroid and cyclosporine therapy was started, but further episodes were noted in both eyes. The patient was then switched to intravenous infliximab, with complete resolution of the inflammation after the second infusion. CONCLUSION: Episcleritis and papillitis should be added to the list of uncommon manifestations of pediatric Behçet's disease. Infliximab is an effective, new therapeutic approach for Behçet's disease that is refractory to the conventional corticosteroid and immunosuppressive therapy.